Freestanding germanene nanosheets for rapid degradation and photothermal conversion. (August 2021) - Ge, M.; Zong, M.; Xu, D.; Chen, Z.; Yang, J.; Yao, H.; Wei, C.; Chen, Y.; Lin, H.; Shi, J.
Abstract: Germanium plays an important role in biomedical utilizations, mainly for inducing erythropoietic, antimicrobial, antiviral, antimutagenic, and immunomodulating effects. The biological applications of organic germanium have been gradually reported in recent years; however, the intrinsic poor biodegradation of most inorganic nanomaterials prevent their further in vivo applications and clinical translation in biomedicine. Herein, two-dimensional (2D) quasi-freestanding and fully biodegradable germanene nanosheets have been synthesized from Zintl-phase ladder-shaped binary germanide (CaGe2 ), which feature intriguing physiochemical properties for photo-triggered therapeutics and photoacoustic diagnostic imaging, as well as excellent biocompatibility, in addition to the excellent degradability compared with other typical 2D biomaterials. This work presents a novel type of 2D structured inorganic germanium biomaterial featuring attractive biomedical multifunctionalities, which is expected to benefit clinical and translational medicine.